THE LEGAL PROTECTION FOR THE CONSUMER OF BUSINESS OPPORTUNITY VENTURES IN INDONESIA - Astrid Amidiaputri Hasyyati; Koesrianti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The understanding about Business Opportunity Ventures in Indonesia has not been entirely in accordance with what is indeed offered as from the origin country. The lack of understanding makes the business fraught with deception and/or injustice in doing business. The purpose of the study is to determine the form of legal protection for business opportunity ventures. The focus of the study discusses the means of legal protection for the consumer. The result obtained was legal protection for the consumer of Business Opportunity Ventures in accordance with the Article 1338 BW. In this protection, an agreement was applicable as the Law for the parties that made it or in its doctrine was Pacta Sunt Servanda. The parties must carry out their respective achievement if the parties did not meet the achievement, then the other parties could demand and take the legal effort through the dispute resolution agency which has been agreed in the agreement.